Viva Puerto Rico [videorecording (DVD)] - Fison, Peter; Smits, Jimmy; Woodcock, George; Holbrook, Rick (PBS, 2017)
Puerto Rico is a tropical island infused with unique natural wonders - from the deepest sea-trench to the longest underground cave system; from a startlingly bright bioluminescent bay to vast rain forests that sometimes really do rain frogs. Explores the wildlife of Puerto Rico and documents attempts for conservation of manatees, parrots, and turtles.